Effect of a novel low-concentration hydrogen peroxide bleaching gel containing nano-sized sodium trimetaphosphate and fluoride - Nunes, Gabriel Pereira [UNESP]; Marques, Mariana Takatu [UNESP]; de Toledo, Priscila Toninatto Alves [UNESP]; Alves, Renata de Oliveira [UNESP]; Martins, Tamires Passadori [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Elsevier, 2024)
Objectives: To evaluate in vitro the effects of nano-sized sodium trimetaphosphate (TMPnano) and sodium fluoride (F) added to a 17.5 % hydrogen peroxide (H2O2) bleaching gel on the color change, enamel mechanical and morphological properties, and H2O2 transamelodentinal diffusion. Materials and Methods: Bovine enamel/dentin discs (n = 180) were divided according to the bleaching gel: 17.5 % H2O2 (17.5 % HP); 17.5 % H2O2 + 0.1 % F (HP/F); 17.5 % H2O2 + 1 % TMPnano (HP/TMPnano); 17.5 % H2O2 + 0.1 % F + 1 % TMPnano (HP/F/TMPnano) and 35 % H2O2 (35 % HP). The gels were applied for 40 min on three sessions, each session spaced 7 days apart. The total color change (ΔE*ab) according to the Commission Internationale de l'Eclairage (CIE) L*a*b* color change measured by CIEDE2000 (ΔE00), whitening index (ΔWID), surface hardness (SH), surface roughness (Ra), cross-sectional hardness (ΔKHN), and transamelodentinal diffusion were assessed. Enamel surfaces were examined using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDS) analysis. The data were analyzed using ANOVA, followed by the Student-Newman-Keuls test (p < 0.05). Results: ΔE*ab, ΔE00, and ΔWID values were comparable among the gels that produced a bleaching effect post-treatment (p < 0.001). The HP/F/TMPnano group exhibited lower mineral loss (SH and ΔKHN), Ra, and H2O2 diffusion compared to the 17.5 % HP and 35 % HP groups, which had the highest values (p < 0.001). SEM/EDS analysis revealed surface changes in all bleached groups, though these changes were less pronounced with F/TMPnano. Conclusions: The 17.5 % HP gel containing F/TMPnano maintains the bleaching effect while reducing enamel demineralization, roughness, H2O2 diffusion, and enamel morphological changes. Clinical Relevance: Low-Concentration H2O2 bleaching gel containing F/TMPnano can be used as a novel approach to enhance safety and maintain the performance of aesthetic effects.
Keywords: Hydrogen peroxide; Nanoparticles; Phosphates; Sodium fluoride; Tooth bleaching agents